Membangun Resiliensi Pangan dengan Memanfaatkan Ekonomi Sirkular di Kabupaten Bogor - Hotimah, Oot; Zain, Alya Nisrina (ECOTAS, 2024)
Food is one of human primary need and in accordance to the twelfth poin of Sustainable Development Goals, there need to be a collaboration between the government body, communities, civil society, private sectors, and researchers. In addition to ending starvation, food production needs to be done with sustainability in mind, which not only focusing on increasing harvests, but also pay attention to environmental aspect generated in food production or/and consumption. The need of food is increasing along with the increasing of population in various cities, there’s a need for systematic transformation by applying the concept of circular economy, therefore to ensure the continuity of the use of the agricultural sector to meet basic needs, as a form of adaptation, namely by reusing product waste into more useful resources in the food production process in the next cycle.